Service‐aware bidirectional throughput optimisation route‐selection strategy in long‐term evolution‐advanced networks. Issue 4 (1st December 2014) - Sun, Chen; Wang, Weidong; Cui, Gaofeng; Wang, Xiaojun
Abstract : Relaying is a promising technology in time‐division duplexing long‐term evolution‐advanced networks to improve cell‐edge performance. Owing to the great degree of difference between the transmitting power of evolved node B and relay nodes, uplink performance and downlink performance sometimes cannot be optimised simultaneously. As an important aspect of radio resource management, the conventional route‐selection strategies optimise either downlink performance only or uplink performance only. However, the users launching different types of services have different requirements in uplink and downlink. By taking service type into consideration, an adaptive bidirectional optimisation (ABO) route‐selection strategy is proposed to adaptively and dynamically optimise uplink and downlink performance. The objective of the proposed ABO strategy is to maximise the user bidirectional throughput which is the sum throughput of uplink and downlink. Moreover, load balancing is considered in the formulation of the proposed strategy. Through system‐level simulation, it can be seen that the proposed strategy is better than the benchmark strategies in different frame configurations.